2018
DOI: 10.1097/mlr.0000000000000860
|View full text |Cite
|
Sign up to set email alerts
|

Weekend Surgical Care and Postoperative Mortality

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…We did not find significant differences in the mortality of patients who underwent ETI in the daytime and off-hours. A previous study indicated that admission on the weekend was associated with a significantly increased mortality compared with that of a midweek admission [ 2 , 17 , 18 ] . Various factors have been attributed to the difference between mortality in daytime and off-hours, such as the availability of senior specialists, the number of skilled nursing staff, and human factors, such as sleep deprivation and fatigue [ 19 , 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…We did not find significant differences in the mortality of patients who underwent ETI in the daytime and off-hours. A previous study indicated that admission on the weekend was associated with a significantly increased mortality compared with that of a midweek admission [ 2 , 17 , 18 ] . Various factors have been attributed to the difference between mortality in daytime and off-hours, such as the availability of senior specialists, the number of skilled nursing staff, and human factors, such as sleep deprivation and fatigue [ 19 , 20 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Healthcare interventions on weekends have been associated with increased mortality and adverse clinical outcomes [111], but these findings are inconsistent [1215]. The overall interpretation of studies of different populations, healthcare systems, and procedures has generated much controversy and debate regarding the possibility of a “weekend effect” impacting the quality of healthcare [10,16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent systematic review and meta-analysis, which is by far the best methodological tool, the odds ratio for postoperative mortality increased from Monday to Friday. 8 If it were true that postoperative complication rates are higher when elective surgery is on a Friday, compared with operations performed earlier in the week, this would have important implications for informed consent and public health. Our results revealed no association between the day of the week when the surgery took place and morbidity.…”
Section: Discussionmentioning
confidence: 99%